Clinical manifestations of coronary artery embolism due to heart tumors - R.M. Vitovsky; V.V. Isaіenko; O.V. Kupchinsky; I.V. Martyschenko; M.M. Serdyuk (Кардіохірургія та інтервенційна кардіологія)
The aim – to present the features of the clinical manifestations and course of two cases of embolism of the coronary arteries, in which fragments of left atrial (LA) tumors served as the embolic substrate.